Overview from Sopron: hungarian employment trends in Austria - Balázs, Ferenc (Studia Mundi – Economica, 2019)
In my study I will look at trends, which characterize the employment practises of Hungarians in Austria over the last 10-15 years. My reference point is the city of Sopron, which has become one of the most important destinations of internal migration in Hungary. Following the summary of the foregoing, I give an overview of the role changes in the cities near the border, and then focus on the specificity of Hungarian migration trends towards Austria. In the light of my primary research results, I present how new and old inhabitants of Sopron relate to migration question, the meaning they attach to the terms „Soproni” (the meaning of living in Sopron) and „Sopronism”, and the reasons that they would suggest if they moved out of to city. In conclusion, I highlight the role of labour migration in reorganizing the spatial structure of border regions. My research results have highlighted the fact that the changing spatial structure requires a novel approach to administrative regulation, shifting the attention of policy